Hans Kelsen’s Position About the Enforcement of Art. 48 WRV in the Light of the Kantian Doctrine of Law - Jiménez Rodríguez, Alba (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This paper sets out a contribution to the interpretation offered by Hans Kelsen to the Staatsgerichtshof decision on 25th.10.1932, about which he confronted with authors like Hermann Heller and Carl Schmitt. The work aims to make clear how Kelsen´s theoretical position is constructed in connection to several key assumptions of Kant´s Practical Philosophy, such as his concept of Imputation (Zurechnung) or his vision of Politics as Executive Doctrin of Law. These thesis are exposed in his main work Critique of Pure Reason (KRV), as also in the Mitschriften of his lessons on Moral Philosophy and Natural Law, included in the last decades in the Academic edition of the Kantian opus.